Perawatan Infeksi Saluran Pernafasan Akut (ISPA) pada Balita - Padila Padila; Henni Febriawati; Juli Andri; Rujung Ali Dori (Jurnal Kesmas Asclepius, 2019)
This study aims to determine the relationship between knowledge and attitudes of mothers with the treatment of Acute Respiratory Infection (ISPA) in children under five in the work area of ​​the Kembang Seri Public Health Center, Talang Empat District, Central Bengkulu District 2018. This type of research is an analytical survey with a cross sectional approach. The results of the univariate analysis research were obtained from 51 respondents, most of the respondents had low knowledge of 21 people (41.2%). While most of the respondents had a bad attitude as many as 27 people (52.9%). Meanwhile, the results of the bivariate analysis of the relationship between knowledge and attitudes of mothers with ARI care in toddlers with the Pearson Chi-square test showed that the p_value for knowledge and attitudes of mothers with ARI care was 0.000 ≤ α 0.005, meaning that there was a significant relationship between knowledge and attitudes of mothers with ARI care in toddlers. in the working area of ​​the puskesmas. Conclusion, the participation of parents, especially mothers, in participating in health promotion activities at the health center must be scheduled. Keywords: Knowledge, ARI Treatment, Attitude